2018
DOI: 10.1002/ajb2.1142
|View full text |Cite
|
Sign up to set email alerts
|

Partial mycoheterotrophy in the leafless orchid Cymbidium macrorhizon

Abstract: Our results indicated that despite its leafless status, fruiting plants of C. macrorhizon were capable of fixing significant quantities of carbon. Considering the autotrophic carbon gain increases during the fruiting season, its photosynthetic ability may contribute to fruit and seed production. These results indicate that C. macrorhizon should, therefore, be considered a partially mycoheterotrophic species rather than fully mycoheterotrophic, at least during the fruiting stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Suetsugu et al . () recently described a similar trend in an unrelated mixtrophic orchid, Cymbidium macrorhizon . However, this remains poorly supported by belowground data, and the model is mostly based on natural isotopic enrichments, which represent indirect evidence (Lallemand et al ., ).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Suetsugu et al . () recently described a similar trend in an unrelated mixtrophic orchid, Cymbidium macrorhizon . However, this remains poorly supported by belowground data, and the model is mostly based on natural isotopic enrichments, which represent indirect evidence (Lallemand et al ., ).…”
supporting
confidence: 52%
“…Yet, in normal, green individuals, photosynthetic resources are sufficient for fruit formation, and this likely did not select for a stronger fungal exploitation to evolve: in particular, colonization in C. damasonium is at its lowest at the time of fruiting (Roy et al ., ). This explains the persistence of intact photosynthesis in mixotrophic orchids (Bellino et al ., ; Suetsugu et al ., ; F. Lallemand & M‐A. Selosse, unpublished).…”
Section: Discussionmentioning
confidence: 92%
“…Once mycorrhizal fungi have been detected and identified, the next step would be to assess their function in autotrophic, partially and fully mycoheterotrophic plants. Recent studies have shown that, in partially mycoheterotrophic orchids, carbon derived from mycorrhizal fungi mostly supports young spring shoots and below‐ground organs, whereas carbon originating from photosynthesis contributes most to sexual reproduction (Gonneau et al, ; Lallemand et al, ; Suetsugu, Ohta, & Tayasu, ). These results may explain why albino plants fail to produce similar levels of seeds than green plants, but show the same survival rates (Lallemand et al, ; Roy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, Schweiger et al () showed that the 13 C abundances of protocorms in rhizoctonia‐associated orchids fall into two separate groups ( ε = 2.0 ± 0.6‰ vs. 7.7 ± 1.2‰). The low 13 C enrichment factor of the first group strongly suggests that 13 C abundance data cannot be used to infer the trophic mode of adult green orchids that belong to the first group, because, at such low 13 C enrichment factor levels, the mycoheterotrophic contributions could be easily masked by differences in plant physiology (Suetsugu et al, ). The differences in 13 C abundance may be related to the diverse ecological niches and nutritional modes of rhizoctonias, with some being predominantly saprotrophs, while others are endophytes (Selosse & Martos, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that mycoheterotrophic orchids tend to have a higher abundance of 13 C and 15 N than co‐occurring C 3 plants (Bidartondo et al, ; Hynson et al, ; Lee, Yang, & Gebauer, ; Martos et al, ; Ogura‐Tsujita, Gebauer, Hashimoto, Umata, & Yukawa, ), since the ectomycorrhizal or saprotrophic fungi that sustain them have higher relative 13 C and 15 N abundances than neighbouring C 3 plants (Gebauer & Meyer, ; Selosse & Roy, ). Furthermore, partially mycoheterotrophic species, which combine autotrophy and mycoheterotrophy, tend to exhibit 13 C and 15 N abundance profiles midway between those of fully mycoheterotrophic species and autotrophic ones (Gebauer & Meyer, ; Selosse & Roy, ; Suetsugu, Ohta, & Tayasu, ; Suetsugu et al, ). Interestingly, these partially mycoheterotrophic species often associate with ECM‐forming fungi, indicating that the ultimate source of their carbon is the photosynthate produced by the nearby trees (Hynson et al, ; Selosse & Roy, ).…”
Section: Introductionmentioning
confidence: 99%